Cardiac arrest in the delivery room after spinal anesthesia for cesarean section: a case report and review of literature. (17th April 2020) - Comito, Chiara; Bechi, Lorenzo; Serena, Caterina; Checcucci, Vanni; Mori, Emanuele; Micaglio, Massimo; Mecacci, Federico; Petraglia, Felice
Abstract: Cardiac arrest in pregnancy is a rare event due to different cause. When it occurs after spinal anesthesia a cause that can explain this event is the Bezold–Jarish Reflex (BJR). A cardiac arrest occurs in a pregnant women after spinal anesthesia admistered for urgent caesarean section. During this event perimortem caesarean delivery (PMCD) is the rapid surgical way that can improve maternal and fetal outcomes. In this situation, it is very important to have a multidisciplinary team of midwives, obstetricians, anesthetists, neonatologists, intensivists that is able to perform perimortem caesarean delivery according to the guidelines.